The Fluctuating Two-Ray Fading Model with Independent Specular Components - Cortés-Arrabal, José Antonio; López-Martínez, Francisco Javier; París-Ángel, José Francisco; Romero-Jerez, Juan Manuel (IEEE, 2022)
We introduce and characterize the independent fluctuating two-ray (IFTR) fading model, a class of fading models consisting of two specular components which fluctuate independently, plus a diffuse component modeled as a complex Gaussian random variable. The IFTR model complements the popular fluctuating two-ray (FTR) model, on which the specular components are fully correlated and fluctuate jointly. The chief probability functions of the received SNR in IFTR fading, including the PDF, CDF and MGF, are expressed in closed-form, having a functional form similar to other state-of-the-art fading models. Then, the IFTR model is empirically validated using multiple channels measured in rather diverse scenarios, including line of sight (LOS) millimeter-wave, land mobile satellite (LMS) and underwater acoustic communication (UAC), showing a better fit than the original FTR model and other models previously used in these environments. Additionally, the performance of wireless communication systems operating under IFTR fading is evaluated in closed-form in two scenarios: (i) exact and asymptotic bit error rate for a family of coherent modulations; and (ii) exact and asymptotic outage probability.
https://openpolicyfinder.jisc.ac.uk/id/publication/3582?from=single_hit
Keywords: Telecomunicaciones; Sistemas de comunicaciones inalámbricos; Wireless channel modeling; Moment generating function; Multipath propagation; Small-scale fading; Two-ray fluctuation